Grinding the face of the poor - Broadway, Mikael N. (2019)
The personal and individualistic bias of contemporary Bible reading can hide the primary message of Scripture. Attention to communal and social contexts of reading, such as economic and political structures of the time, opens greater understanding of the historical world in which texts are written, as well as the economic and political message for contemporary readers. A re-reading of the first twelve chapters of Isaiah demonstrates the way that psychologizing and spiritualizing texts obscures their relevance to current social conditions. Isaiah addresses sin and idolatry, topics familiar to personalizing readers; however, in Isaiah the topics are tightly interwoven with economic life. Other prominent contemporary issues that take the foreground in Isaiah 1-12 are property foreclosure and seizure, unlivable wages, wage theft, mistreatment of workers, unjust laws favoring the wealthy, influence of money in political systems, and irresponsible leadership. Concepts of Jubilee economics, themes in the Torah and subsequently in Jesus' teaching, pervade the criticism of Israel and Judah in these prophetic texts.
Keywords: Isaiah; Economics; foreclosure; Injustice; Poverty; Wealth